Oral cysticercosis: A rare case presentation with ultrasound and MRI findings - Revath Vyas Devulapalli; Balaji Babu Bangi; Lakshmi Kavitha Nadendla; Archana Pokala (Wolters Kluwer Medknow Publications, 2015)
Taenia solium , the larvae of pork tapeworm, can cause the parasitic infection known as cysticercosis. It is commonly seen in developing countries. The World Health Organization estimates that over 50,000 deaths per year are caused by neurocysticercosis worldwide. It can occur anywhere in the body. Cysticerci in the muscles generally do not cause symptoms; they present as nodules and can be felt as lumps under the skin or they can present as muscular pseudohypertrophy. The condition rarely involves musculature of the orofacial region and presents a difficulty in clinical diagnosis. Here, we present a case report of a healthy middle-aged female patient who had a painless swelling below the lower lip. The ultrasound examination revealed an intramuscular cysticercosal cyst. The diagnosis was confirmed using magnetic resonance imaging and by histopathology. The case was managed by conservative enucleation of the cyst.